FACTORS AFFECTING COMMUNITY PARTICIPATION IN MANGROVE TOURISM DEVELOPMENT IN PUDANG VILLAGE, BINTAN REGENCY: FAKTOR - FAKTOR YANG MEMPENGARUHI PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN WISATA MANGROVE DI DESA PENGUDANG KABUPATEN BINTAN - Haidawati, Haidawati; Fitria Ulfah; Tantri Silvani (MarIslands, 2024)
Pengudang Village is a tourist village located in Bintan Regency. The main tourist attraction in Pengudang Village is mangrove tourism. Mangrove tourism has its own charm for tourists, especially foreign tourists. Mangroves in Pengudang Village are very beautiful and their habitats are maintained, this cannot be separated from the participation of the community because their management is community-based. The importance of community participation in supporting the development of mangrove tourism, because effective development requires involvement (participation) from various parties (stakeholders), especially the community. The purpose of this research is to find out the driving factors and inhibiting factors for community participation in the development of mangrove tourism in Pengudang Village. The research uses qualitative research methods. Determination of the sample is 10% of the total